Filtro Ativo Trifásico Shunt com Número Reduzido de Indutores - Gomes, Zariff Meira (2015)
This work presents an active power filter for three-phase three-wire systems without an inductor when compared to the usual structure of a shunt active power filter. For the determination and control of the references it was used the Park’s transformation, it means that all control was done in synchronous axes. The active filter of this work is in parallel configuration acting therefore as a current source and should correct the power factor and current harmonics selectively of the power grid. Simulation results were presented validating the control strategy.